Valence-band structure and critical point energies of diamond along [100] - Edmonds, M.; Tadich, A.; Wanke, M.; O’Donnell, Kane; Smets, Y.; Rietwyk, K.; Riley, J.; Pakes, C.; Ley, L. (American Physical Society, 2013)
Accurate valence-band dispersions E(k⊥) have been determined for the technologically relevant Γ-Δ-X symmetry direction of hydrogen-terminated diamond (100) using normal emission angle-resolved photoemission spectroscopy for photon energies between 30 and 206 eV. By analyzing the data using a free-electron final-state model, the emission features can be well understood by assuming primary cone transitions. Critical point energies in the valence band are in good agreement with self-consistent quasiparticle GW calculations. Substantial modulations in the valence-band dispersion occurring in specific regions of the Brillouin zone have been traced to band crossings in the unoccupied free-electron final state. A one-band effective mass of (0.39 ± 0.30)m0 is determined from the band dispersion close to the Γ point and compared with values in the literature.